Application of Multi-Criteria Decision-Making in Achieving the Right Mix Asphalt Mixtures - A. A. Rassafi; M. Zarei; A. Dadashi (Electronic Journal of Structural Engineering, 2021)
Marshall Test is one of the tests used for asphalt mixture. This test has six parameters, including stability, unit weight, flow, void in mineral aggregate, voids in total mix, and voids filled with asphalt. Further, the additional cost of various additives to the asphalt mixture for building one kilometer of the road is a negative parameter. However, using additives improves the technical characteristics of the asphalt mixture. Therefore, making a proper choice among the alternatives would be a hard task. This paper tries to provide an appropriate method for mixing the design of asphalt mixtures to select the best alternative by considering all technical criteria. For this purpose, the concordance analysis method, which is one of the compensation models of the Multi-Criteria Decision-Making (MCDM), was used. The results showed that the concordance analysis method using a pairwise comparison strategy combines the different criteria to prioritize alternatives and to propose the best alternative. Therefore, this method can be used as a superior method for mixing the design of asphalt mix compared to conventional methods.